2020
DOI: 10.1177/1077801219892648
|View full text |Cite
|
Sign up to set email alerts
|

Do Negative Emotional States Play a Role in the Association Between Intimate Partner Violence and Poor Health-Related Quality of Life in Chinese Women From Low-Income Families?

Abstract: A cross-sectional analysis of a dataset of 156 participants in a health assessment program explored whether negative emotional states mediated the association between intimate partner violence (IPV) and health-related quality of life (HRQoL). Compared with IPV screen-negative participants, those who screened positive had significantly lower HRQoL and significantly higher levels of depression, anxiety, and stress. The inverse associations between the presence of IPV and HRQoL were found to be mediated by depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
0
8
0
2
Order By: Relevance
“…Consequently, with the reality surrounding this problem, during the last 5 years, intensive treatments have emerged for women who experience the trauma associated with exposure to physical, psychological and sexual violence, with the aim of addressing and overcoming the effects caused physically and mentally (17,18). Many studies have shown therapeutic treatments with benefits at the cognitive, emotional and social levels in female victims; however, they have not yet demonstrated a comprehensive effectiveness among patients (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, with the reality surrounding this problem, during the last 5 years, intensive treatments have emerged for women who experience the trauma associated with exposure to physical, psychological and sexual violence, with the aim of addressing and overcoming the effects caused physically and mentally (17,18). Many studies have shown therapeutic treatments with benefits at the cognitive, emotional and social levels in female victims; however, they have not yet demonstrated a comprehensive effectiveness among patients (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Tavoli et al [27] and Gharacheh et al [34] reported that in Iran, domestic violence during pregnancy is negatively correlated with healthrelated quality of life. Behford et al [40] reported that in China, the health-related quality of life was considerably lower in women experiencing sexual violence by their partner.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-accepted that women who had experienced IPV were at higher risk of both mental and physical impairment, as well as premature death ( 4 7 ). A large body of evidence has further revealed that the detrimental impact of IPV against mothers could also extend to the next generation, leading to delayed development, poorer physical health, and more psychosocial problems in their children ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%